(untitled) (Fiep Bulletin - online, 2011)
The Diabetes Mellitus (DM) is a syndrome of multiple aetiology, due to the insulin lack and the capacity of that hormone to do their effects appropriately. It is characterized by chronic hyperglycemia, frequently accompanied of dyslipidemia, arterial hypertension and endothelial dysfunction. The dyslipidemia is one of the main risk factors for DCV in diabetic patients, whose influence is larger than the others. The more frequent lipidic alterations in the population correspond to hypertriglyceridemia (increase in the triglycerides levels), HDL-c low and qualitative alterations in the lipoproteins, such as the formation of particles of LDL-c small and dense. With these premises, the work aimed to evaluate the association of DM type 2 and dyslipidemia. It was treated as a descriptive and longitudinal study, performed in the Servicio Municipal de Salud (SMS) and in the Laboratory of Clinical Analyses of the Universidad Estatal de Paraíba, UEPB, whose appraised parameters were fast glycemia, triglycerides, total cholesterol and fractions. The data was appraised through percentile statistics. Of the 57 patients, most were women and 81% of the samples were dyslipidemic. Regarding dyslipidemia risk factors, the most representative were DM and Central Obesity. Most demonstrated associated hypercholesterolemia the hypertriglyceridemia; the HDL-c was altered in 41% of the men and in 55% of the women DM, in spite of being a degenerative chronic disease that is not contagious, it makes possible a larger lifespan to their bearers when they adhere to treatment. Therefore, the population in study needs to be more motivated to accomplish a balanced diet and to practice physical activities, and once these cares are attended, they will reduce the glycemia and lipid levels contributing to a healthier longevity.